Manual de Apoio à Reabilitação de Edifícios das Décadas de 60, 70 e 80 - João Pupo Correia Salgado Lameiras (2010)
Refurbishment has become a major concern of the construction sector throughout Europe. While the need for new construction declines, the building stock needs interventions that requalify and renew it. Portugal is one of the countries where the rehabilitation rates are lower: there is still a lot of construction activity with low levels of maintenance and renewal. Although this is a growing market with huge potential, there are still some technical, financial and policies related difficulties for the players in the industry to motivate themselves to invest in it. In this context of rehabilitation, great importance has been given to the monumental and antique buildings. However, buildings constructed since the middle of last century and even the more recent ones are also starting to show some lack of intervention. These buildings present a great difference from the first ones: the fact that they are, in the Portuguese case, mostly built of reinforced concrete porches. This material, which began to be used generally in the 60's, proved to be less durable than what would be expectable. In addition, a multitude of new techniques and building systems began to be used on a large scale without full knowledge of their long-term behaviour. It is in this context that this work emerges. Only the buildings constructed between 1960 and 1985 will be focused, because they bring together a set of characteristics that allow us to categorize and separate them from the other ones: the antique and the recent ones. This document is solely a contribution to a manual with detailed technical information for the refurbishment of buildings of this season. This work will begin by leading the reader throughout the current state of the segment of rehabilitation in Portugal and in Europe. Subsequently, based on a sample of projects collected from a specialized company, a description of the typical features of these buildings and the pathologies that more often they are subjected to will be made. Then the work will focus and present a group of techniques to be applied to each of the elements described and, at last, it will be presented the average cost of those solutions, bearing in mind that these solutions will never be associated directly to the pathologies but only to the affected elements. KEYWORDS: Refurbishment, Reinforced Concrete, Pathologies, Solutions, Costs.